Roles of CXCL1 and CXCL2 on neutrophils during immune complex-mediated inflammation - Li, Jackson Liangyao (2015)
CXCR2 is a critical regulator of neutrophil migration, and has been proposed to play an important role in immune complex-mediated inflammation. In the mouse, major pro-inflammatory CXCR2 ligands include CXCL1/KC/GRO-α and CXCL2/MIP-2a/GRO-β, but their specific individual roles on neutrophils have remained largely unclear. We developed an intravital multiphoton microscopy model of the reverse passive Arthus reaction in the mouse ear skin that allowed us to image neutrophil interactions with immune complexes. In combination with other in vitro and in vivo assays, we discovered that both CXCL1 and CXCL2 played very similar roles on neutrophil activation, but CXCL2 was the major chemokine produced by the neutrophils in feed-forward and autocrine loops, whereas CXCL1, produced by sentinel cell types such as macrophages and endothelial cells, could enhance neutrophil CXCL2 production. Our study reveals the complexity of CXCR2 ligand crosstalk during immune complex-mediated inflammation, and elucidates an intriguing mechanism of neutrophil biology. Keywords: neutrophil, immune complex, inflammation, CXCR2, CXCL1, CXCL2, in vivo imaging, multiphoton microscopy